2018
DOI: 10.1515/polyeng-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of biodegradable polymer/nano-hydroxyapatite bioceramic scaffold for spongy bone regeneration

Abstract: Abstract Biodegradable polymer/bioceramic composite scaffolds can overcome the limitations of conventional ceramic bone substitutes, such as brittleness and difficulty in shaping. To better mimic the mineral components and microstructure of natural bone, a novel nano-hydroxyapatite (nHAp)–chitosan composite scaffold including gelatin and polymer (poly(lactic acid)) with high porosity was developed using a sol-gel method and subsequently lyophilized for efficient bone tissue eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Coe et al reported that compressive strength is 150 MPa for compact bones, 4–15 MPa for spongy bone, 161.289 MPa for 1MCG-P, 178.239 MPa for 2MCG-P, and 183.966 MPa for 5MCG-P. The proposed bone scaffolds in this study have comparable compressive strength with compact bones [ 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 51%
“…Coe et al reported that compressive strength is 150 MPa for compact bones, 4–15 MPa for spongy bone, 161.289 MPa for 1MCG-P, 178.239 MPa for 2MCG-P, and 183.966 MPa for 5MCG-P. The proposed bone scaffolds in this study have comparable compressive strength with compact bones [ 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 51%
“…Compared to other biocomposites, a significant increase in 1% HA was observed and the increase was expected to continue after 1 percent due to its compact nature 23 , but the desired increase could not be achieved. It is assumed that when the nanostructure incorporated more than 1 percent of PUF, total homogeneity in the mixture was not achieved.…”
Section: Resultsmentioning
confidence: 95%
“…4 b, the sample with the lowest total weight loss is PUF containing 5% HA. TGA results noticeably present that the higher the amount of HA in biocomposites, the higher the thermal stability 23 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, chitosan by itself is not osteoconductive and thus combined with biopolymers or bioactive nanoceramics such as SiO 2 , ZrO 2 , TiO 2 , HAP, etc. that enhances mechanical potency and structural reliability of chitosan-based composites for bone tissue engineering applications [117][118][119][120][121].…”
Section: Chitin/chitosanmentioning
confidence: 99%